A new convergent conjugate gradient method under the exact line search - Mustafa, Mamat (2014)
Conjugate gradient methods are widely used for unconstrained optimization problems, especially large scale problems. That is, for its simplicity, low memory requirement, and global convergence properties. In this paper, we study the global convergence properties of a new conjugate gradient method under the exact line search. Under some assumptions, the proofs of the sufficient descent property and the global convergence are given. The numerical results show that our new method is efficient for some unconstrained optimization problems.